Perceptions and opinions of Jamaicans on Caribbean institutions for regional integration - Tindigarukayo, Jimmy Kazaara (2006)
Analyzes the perceptions and opinions of 1581 Jamaicans of voting age, on Caribbean institutions for regional integration. Concentrates on the information relating to the Caribbean Single market and Economy.